Value chain mapping: A novel approach for market dynamics analysis in tomato (Solanum lycopersicum) - DUBEY, SHANTANU KUMAR; GILLS, RESHMA; GAUTAM, U S; SINGH, ATAR; BURMAN, R R; SINGH, RAJEEV (The Indian Journal of Agricultural Sciences, 2020)
The present investigation is an attempt to map the tomato (Solanum lycopersicum L.) value chains existing in the Champawat district of the Uttarakhand (during 2016–17) to know the market dynamics in it. Estimation of production dynamics showed an average cost of production of tomato as ₹ 80077/ha with an average net return of ₹ 158123/ ha. Data collected from the study area revealed the existence of two marketing channels with different players and interconnection (C1: Producer- Retailers-Consumer and C2: Producer -Whole sellers – Retailers-Consumers) on which tomato farmers were dependent to reach the final consumers. Value chain mapping revealed that producers share in consumers’ price in net benefit terms for C1 was 52.06% and for C2 was 27.06% though the value added for tomato till reaching the final consumers in both channels were apparently same. This showed the necessity of tactical policy integration in value chain procedural development in tomato. Reforms are also needed in the existing marketing mechanism to make a change in it, in an ‘actor-activity-client oriented beneficial and profitable’ direction.